Penentuan Prioritas Pendaftaran Tanah Sistematis Lengkap Melalui Clustering Jumlah Sertifikat Hak Atas Tanah Menggunakan K-Means - Hanaki Restu Putri; Maimunah Maimunah; Endah Ratna Arumi (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
In carrying out its duties and functions to serve the community in the land sector, BPN Magelang Regency is still experiencing several obstacles such as in terms of filing and determining service priorities in 21 sub-districts in Magelang Regency. To improve the quality of BPN services in Magelang Regency, this research will build a system to assist file management and grouping of service priorities by implementing the K-Means Clustering method. The K-Means Clustering method was chosen because this method can calculate the grouping of several alternatives based on the criteria. The result of this study is that the application of a synchronized web-based PTSL application can make it easier for PTSL officers to manage land title registration files. In addition, the integration of K-Means Clustering calculations that are implemented into the system can be used as an approach tool in determining which districts are the priority for handling land certificate.